1982
DOI: 10.1210/jcem-55-1-175
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Response to Metoclopramide in Hyperthyroidism

Abstract: The response of PRL to the oral administration of the dopamine receptor-blocking agent metoclopramide and the effect of metoclopramide on the TRH-induced release of PRL and TSH were measured in eight patients with hyperthyroidism and in eight age- and sex-matched euthyroid controls. As expected from the known direct inhibitory influence of thyroid hormones on pituitary TSH secretion, there was no TSH rise in response to metoclopramide in either group. PRL levels, on the other hand, rose significantly after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 9 publications
3
11
0
Order By: Relevance
“…This study confirmed that thyroid hormones exert neg ative feedback effects on the basal and TRH-stimulated PRL secretion in humans [1][2][3][4][5][6][7], In the hyperthyroid patients, not only the basal PRL level but also the PRL responsiveness to TRH were significantly lower during the hyperthyroid state than during the euthyroid state. In turn, in the hypothyroid patients both variables were sig nificantly higher during the hypothyroid state compared to the euthyroid state.…”
Section: Discussionsupporting
confidence: 79%
“…This study confirmed that thyroid hormones exert neg ative feedback effects on the basal and TRH-stimulated PRL secretion in humans [1][2][3][4][5][6][7], In the hyperthyroid patients, not only the basal PRL level but also the PRL responsiveness to TRH were significantly lower during the hyperthyroid state than during the euthyroid state. In turn, in the hypothyroid patients both variables were sig nificantly higher during the hypothyroid state compared to the euthyroid state.…”
Section: Discussionsupporting
confidence: 79%
“…The rise in both TSH and PRL is reported as significantly greater in subclinical than in overt hypothy roidism and interpreted as a stimulation of hypothalamic DA release induced by thyroid hormones [3]. This hypothe sis appears to be in line with the blunted PRL response to metoclopramide in hyperthyroidism [10]. In our study, after exogenous administration of thyroxine, the magnitude of the TSH rise in response to TRH was reduced to values found in euthyroid subjects, and the marked rise in plasma TSH after the DA receptor antagonist administration com pletely disappeared.…”
Section: Discussionmentioning
confidence: 60%
“…It has also been suggested that an altered thyroid function can modify the control of TSH and PRL, both at the hypothalamic and pituitary levels [3,10].…”
mentioning
confidence: 99%
“…Regarding the elevation of the basal PRL level in the hypothyroid state, the following possibilities can be considered ; 1) negative feedback effect of thyroid hormones on the lactotrophs, as it is reported that elevated thyroid hormones have a direct suppressive effect on the pituitary lactotrophs (Sawers et al 1982), 2) decreased hypothalamic dopaminergic regulation on these cells or 3) increased TRH secretion (Feek et al 1980). From these explanations, the paradoxical elevation of the basal PRL level observed in this study is difficult to understand.…”
Section: Resultsmentioning
confidence: 81%
“…Contreras et al (1981) have postulated depressed hypothalamic dopaminergic tone in patients with hypothyroidism based on their findings that the patients showed the inadequate PRL response to dopamine receptor blocker. However, the exact relationships between thyroid function and hypothalamic dopaminergic activity are not fully studied (Sawers et al 1982). In order to evaluate these relationships, we examined the changes of basal PRL, TSH and their responsiveness to sulpiride (a dopamine receptor blocker) in patients with primary hypothyroidism, untreated or treated with thyroid replacement therapy.…”
mentioning
confidence: 99%